2020
DOI: 10.1080/13811118.2020.1783410
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Suicidal Ideation in Patients Hospitalized for Depression: An Exploratory Study Using Smartphone Ecological Momentary Assessment

Abstract: This study used ecological momentary assessment (EMA) to explore the correlates of suicidal ideation (SI) instability in patients hospitalized for depression and SI. Thirty-nine adult inpatients were given smartphones with visual analogue scales to rate current depressed mood, anger/irritability, feeling socially connected, and SI three times a day throughout hospitalization. Affective Lability Scales (ALS) were also completed at baseline. SI instability was correlated with SI intensity, depressed mood instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…The number of (scheduled) EMA prompts per day ranged from 1 to 11 (median = 5, n = 21). All studies used some form of signal-contingent sampling: (pseudo)random sampling schedules were most frequently used [57%, n = 13 (42,47,51,58,61,65,69,71,79,83,85,86,88)], followed by fixed sampling [26%, n = 6 (45,66,67,72,80,82)], and protocols that combined both fixed and (pseudo)random sampling [13%, n = 3 (47,56,60)]. Fixed schedules were almost exclusively used in studies with once-daily prompts (as well as three older studies with PDAs (45,81,82)), whereas pseudorandom schedules were typically used for repeated withinday assessments.…”
Section: Schedulesmentioning
confidence: 99%
“…The number of (scheduled) EMA prompts per day ranged from 1 to 11 (median = 5, n = 21). All studies used some form of signal-contingent sampling: (pseudo)random sampling schedules were most frequently used [57%, n = 13 (42,47,51,58,61,65,69,71,79,83,85,86,88)], followed by fixed sampling [26%, n = 6 (45,66,67,72,80,82)], and protocols that combined both fixed and (pseudo)random sampling [13%, n = 3 (47,56,60)]. Fixed schedules were almost exclusively used in studies with once-daily prompts (as well as three older studies with PDAs (45,81,82)), whereas pseudorandom schedules were typically used for repeated withinday assessments.…”
Section: Schedulesmentioning
confidence: 99%
“…Third, MI holds a temporal property since mood uctuations can change from moment to moment, which is unlikely to be recalled accurately, such as which day and what time during the day it occurred (102). Two recent studies reported that paper-and-pen measures of MI do not agree with smartphone measured MI (103,104). Finally, the VAS used to assess antenatal MI is not previously validated.…”
Section: Discussionmentioning
confidence: 99%
“…The program was delivered using the Ethica platform co-designed and codeveloped by the coauthor NO and Ethica Data Services. The Ethica platform is designed to aid in the creation, delivery, and data collection of smartphone-based apps [ 36 , 37 ]. A computer science student (JN) customized functionalities on the Ethica system to reflect the co-designed program.…”
Section: Methodsmentioning
confidence: 99%